Hypoxia in the Bohai Bay, China: distributions, causes and mechanisms - Zhang, Guodong; Wen, Yujian; Ding, Changling; Zhang, Guicheng; Sun, Jun (Frontiers in Marine Science, 2023)
The Haihe River system is a major conduit of land-based pollution into the Bohai Sea in North China, This study presented the first-ever observation of hypoxia in the Haihe River estuary, providing valuable insights into the complex interplay between physical and biochemical factors influencing hypoxia in estuarine systems. The research found seasonal variations in DO distribution in the estuaries of the Haihe and Yongdingxin Rivers. Hypoxia emerged in summer at the bottom of the Haihe River estuary and dissipated in autumn, with the minimum DO concentration of 1.85 mg/L recorded at the bottom of the HH-2 station. Within the hypoxic zone, the average DO concentration was 4.02 mg/L, and the average of DO saturation was less than 0.4. This study also identified the primary drivers of summer hypoxia as a combination of physical and biochemical factors, with water stratification due to hydrodynamic factors limiting exchange and reoxygenation between different water layers. In addition, the decomposition of organic matter in the bottom consumed a significant amount of dissolved oxygen.The significantly higher DO concentration and saturation in autumn compared to summer suggested the possible existence of seasonal hypoxia in the Haihe estuary. This study of hypoxia in the Haihe River estuary contribute to a better understanding of the factors that influence seasonal hypoxia. The findings have important implications for the management and remediation of hypoxia in the Haihe estuary and other estuarine systems.